2000
DOI: 10.1007/bf02976584
|View full text |Cite
|
Sign up to set email alerts
|

Developmental patterns of mST3GaIV mRNA expression in the mouse:In situ hybridization using DIG-labeled RNA probes

Abstract: mST3GalV synthesizes ganglioside GM3, the precursor for simple and complex a- and b- series gangliosides, and the expression and regulation of mST3GalV (CMP-NeuAc: lactosylceramide alpha2,3-sialyltransferase) activity is central to the production of almost all gangliosides, a class of glycosphingolipids implicated in variety of cellular processes such as transmembrane signaling, synaptic transmission, specialized membrane domain formation and cell-cell interactions. To understand the developmental expression o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Ganglioside GM3 was synthesized by mST3GalV, and the expression and regulation of mST3GalV (CMP-NeuAc: lactosylceramide alpha-2, 3-sialyltransferase) activity is central to the production of almost all gangliosides. Spatial and temporal expression of mST3GalV mRNA (GM3) during mouse embryogenesis [on embryonic (E) days E9, E11, E13, and E15] was demonstrated by in situ hybridization with digoxigenin-labeled RNA probes (Ji et al, 2000, Table 1). All tissue samples obtained on E9 and E11 were observed to have the same level of mST3GalV mRNA expression.…”
Section: Gangliosides In Mouse Embryonic Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Ganglioside GM3 was synthesized by mST3GalV, and the expression and regulation of mST3GalV (CMP-NeuAc: lactosylceramide alpha-2, 3-sialyltransferase) activity is central to the production of almost all gangliosides. Spatial and temporal expression of mST3GalV mRNA (GM3) during mouse embryogenesis [on embryonic (E) days E9, E11, E13, and E15] was demonstrated by in situ hybridization with digoxigenin-labeled RNA probes (Ji et al, 2000, Table 1). All tissue samples obtained on E9 and E11 were observed to have the same level of mST3GalV mRNA expression.…”
Section: Gangliosides In Mouse Embryonic Developmentmentioning
confidence: 99%
“…All tissue samples obtained on E9 and E11 were observed to have the same level of mST3GalV mRNA expression. On E13, mST3GalV mRNA was expressed in various neural and non-neural tissues and in the telencephalon, while on E15, strong expression of mST3Gal V was observed in the liver (Ji et al, 2000). Bouvier and Seyfried (1989) observed that the predominant gangliosides in E12 mouse embryos were GD3 (51% of total sialic distribution), GM3 (19%), and GT1b (9.6%); other gangliosides occurred in much lower amounts (GM2 (2.6%), GM1 (1.6%), GD1a (3.7%), GD1b (6.3%), and GQ1b (4.5%)).…”
Section: Gangliosides In Mouse Embryonic Developmentmentioning
confidence: 99%
“…These gangliosides are thought to be involved in the control of several biological processes, including apoptosis, mouse embryonic development, cell proliferation, cell surface interactions, cell differentiation, and transmembrane signaling (10,11). GM3 is mostly expressed during embryogenesis in mice (12,13), but its expression is decreased during brain development (14). GD1a is also expressed during late embryogenesis (E9-E16), and increased expression of GD1a is observed during mouse brain development (12,14).…”
Section: Introductionmentioning
confidence: 99%
“…GM3 is mostly expressed during embryogenesis in mice (12,13), but its expression is decreased during brain development (14). GD1a is also expressed during late embryogenesis (E9-E16), and increased expression of GD1a is observed during mouse brain development (12,14). In particular, GM1 has been shown to possess antineurotoxic, neuroprotective, and neurorestorative capabilities, as well as the ability to facilitate neuronal commitment (15,16).…”
Section: Introductionmentioning
confidence: 99%
“…Sialyated glycosphingolipids from the ganglio-series are normally classified into four series from 0-to c-series and shed actively into the tumor microenviroment (Svennerholm 1980;Kudo et al 2003). Human normal tissues express various gangliosides of 0-and a-series (Ji et al 2000;Yamashita et al 1999) and its complex expression is increased under manifold pathological disorders (Ariga et al 2008), immune diseases (Shahrizaila and Yuki 2011), and cancer (Bobowski et al 2012). GD3 has been considered a cell death effector because of its ability to interact with mitochondria-mediated apoptosome activation and subsequent apoptosis based on death ligands (Paris et al 2002).…”
Section: Introductionmentioning
confidence: 99%